2009
DOI: 10.1016/j.mad.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased age reduces DAF-16 and SKN-1 signaling and the hormetic response of Caenorhabditis elegans to the xenobiotic juglone

Abstract: Cells adapt to stressors by activating mechanisms that repair damage and protect them from further injury. Stress-induced damage accumulates with age and contributes to age associated diseases. Increased age attenuates the ability to mount a stress response, but little is known about the mechanisms by which this occurs. To begin addressing this problem, we studied hormesis in the nematode Caenorhabditis elegans. When exposed to a low concentration of the xenobiotic juglone, young worms mount a robust hormetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 110 publications
(140 reference statements)
7
90
1
2
Order By: Relevance
“…The model organisms C. elegans and D. melanogaster have also been shown to be capable of adaptation to oxidative stresses through mild exposure to heat shock, 100% oxygen or the redox quinone juglone in worms, and heat shock or irradiation in flies (Cypser and Johnson, 2002;Lithgow et al, 1995;Moskalev et al, 2009;Przybysz et al, 2009). The present results demonstrate that both model organisms are capable of such adaptation with H 2 O 2 pre-treatment.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The model organisms C. elegans and D. melanogaster have also been shown to be capable of adaptation to oxidative stresses through mild exposure to heat shock, 100% oxygen or the redox quinone juglone in worms, and heat shock or irradiation in flies (Cypser and Johnson, 2002;Lithgow et al, 1995;Moskalev et al, 2009;Przybysz et al, 2009). The present results demonstrate that both model organisms are capable of such adaptation with H 2 O 2 pre-treatment.…”
Section: Discussionsupporting
confidence: 54%
“…It has been shown that high doses of H 2 O 2 (10mmoll -1 ) can cause the cytoplasmic to nuclear translocation of SKN-1 fused to GFP (SKN-1::GFP) in C. elegans intestinal cells (An and Blackwell, 2003;An et al, 2005). Also, a report by Przybysz and colleagues has shown that with depletion of SKN-1, worms become more susceptible to the oxidant juglone (Przybysz et al, 2009). The SKN-1::GFP line (An and Blackwell, 2003), was crossed with a glo-1 mutant strain to produce worms with reduced non-specific fluorescence.…”
Section: Role Of the 20s Proteasome In H 2 O 2 -Induced Adaptation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them generate ROS to extend lifespan. The botanical pesticides juglone and plumbagin are thought to extend lifespan of C. elegans by generating ROS (Hartwig et al, 2009;Hunt et al, 2011;Przybysz et al, 2009). Low concentrations of paraquat, which is toxic at high concentrations, were reported to extend lifespan of C. elegans by generating ROS from mitochondria (Yang and Hekimi, 2010a).…”
Section: Pqq Is a Lifespan Extension Chemical With A Novel Action Mecmentioning
confidence: 99%
“…This results in transcriptional activation and boosting of antioxidant defence, augmentation of detoxification processes or of the protein quality control system (Itoh et al 1997;Itoh et al 1999;DinkovaKostova et al 2001). Naturally occurring quinones (such as juglone, vitamin K, plumbagin) bearing α,β-unsaturated carbonyl moieties represent typical xenohormetics (Shibayama-Imazu et al 2006;Przybysz et al 2009;Son et al 2010). Furthermore, flavonoids might represent precursors of xenohormetic molecules and undergo conversion by oxidative metabolism which involves a two-electron auto-oxidation to an electrophilic quinone-type molecule (Metodiewa et al 1999;Awad et al 2000;Bast and Haenen 2002).…”
Section: Ii) Protein Carbonyls Intensitymentioning
confidence: 99%